Promoting Teaching and Learning Through Research-Informed Professional Development: The Leadership for Learning Programme in Australia and China - Iram Siraj; Runke Huang (Education Sciences)
The fragmented provision of training for early childhood educators has highlighted the imperative need for research-informed professional development (PD) programmes to enhance educator professionalism. This study evaluates the effectiveness of a research-informed in-service PD programme—“Leadership for Learning”—through cluster randomised controlled trials in Australia and China. In Australia, the study involved 83 early-years services, and 1346 4–5-year-old children. In China, the study adapted the PD programme both educationally and culturally, involving 24 preschools, 95 classrooms, 202 educators, and 547 children aged 3–5 years. The comparative findings revealed that the PD programme significantly improved scores on the ECERS-E and SSTEW classroom quality rating scales in both Australia and China. Regarding children’s outcomes, the Australian PD programme significantly enhanced children’s numeracy development, social–emotional development, and expressive language, but not vocabulary, while the Chinese adaptation improved literacy development but not numeracy. This study has important implications for the implementation of PD programmes and cross-cultural educational research, highlighting the need for context-specific adaptations to maximise the effectiveness of PD interventions.